Evaluation of the Information System (Smart Deer System) at BKPSDMD of Bangka Belitung Islands Province - Ahmad Fauzi, Aditya (Research Group of Data Engineering, Faculty of Informatics, 2025)
Improving the quality of human resources (HR) is one of the important factors in the development of a region. To realize superior, competent, intelligent, and educated human resources, a fast, easy, and useful information system is needed in the management of further education in the BKPSDMD Prov. BaBel, therefore, introduced an information system called